2000
DOI: 10.2337/diabetes.49.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-secreting cells derived from embryonic stem cells normalize glycemia in streptozotocin-induced diabetic mice.

Abstract: Embryonic stem (ES) cells display the ability to differentiate in vitro into

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
525
2
20

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 809 publications
(554 citation statements)
references
References 14 publications
7
525
2
20
Order By: Relevance
“…Targeted intervention in apoptotic and/or oxidative stress and inflammatory signalling pathways could be one such approach. Such methodology will also be essential, in our opinion, for obtaining the large numbers of highly differentiated insulin-secreting cells envisaged for cell replacement therapy [44] regardless of whether they have been derived by conditional immortalisation of beta cells [4,5], from adult [6] or embryonal [7,8,9] stem cells or by any other means for creating surrogate beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted intervention in apoptotic and/or oxidative stress and inflammatory signalling pathways could be one such approach. Such methodology will also be essential, in our opinion, for obtaining the large numbers of highly differentiated insulin-secreting cells envisaged for cell replacement therapy [44] regardless of whether they have been derived by conditional immortalisation of beta cells [4,5], from adult [6] or embryonal [7,8,9] stem cells or by any other means for creating surrogate beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that pancreatic cell types can be generated from mouse and non-human primate ESCs [10][11][12][13][14][15][16][17][18]. Based on these findings, recent studies have also suggested the potential of hESCs to differentiate into insulin-producing cells through spontaneous in vitro differentiation [5] or the use of a multi-stage protocol [6].…”
Section: Introductionmentioning
confidence: 99%
“…Functional pancreatic cells, however, were successfully generated using lineage selection strategies based on pancreas-specific promoters [5,6], by modified protocols in combination with transgene expression [7][8][9], or by addition of a phosphoinositol-3 kinase inhibitor [10]. The differentiated cells showed properties of (neonatal) beta cells, such as insulin transcripts and C-peptide/insulin co-expression, insulin-secretory granules, ion channel activity of embryonal beta cells, and normalisation of blood glucose level after transplantation into diabetic mice [5][6][7][8][9][10]. Most of the differentiation protocols required a long cultivation period, including 4-5 days of embryoid body (EB) formation, followed by 3-4 weeks of differentiation, and some protocols required genetic manipulation.…”
mentioning
confidence: 99%